What makes the dyspeptic patient feel ill? A cross sectional survey of functional health status, Helicobacter pylori infection, and psychological distress in dyspeptic patients in general practice. (1st July 1999) - Quartero, A O; Post, M W M; Numans, M E; de Melker, R A; de Wit, N J
Abstract : BACKGROUND: Dyspepsia is prevalent in about 30% of the general population in Europe, but only 25% of people with complaints consult their general practitioner. AIMS: To study the relation between the severity of dyspeptic complaints and the health status of patients presenting to the general practitioner; and the relation with patient characteristics, Helicobacter pylori infection, and psychological distress. METHODS: A cross sectional, general practice based survey of 360 unselected primary care dyspeptic patients from 92 general practices in The Netherlands was conducted. Symptom severity was measured using a validated symptom score, H pylori using a whole blood test, and psychological distress using the GHQ-12 test. Functional health status was assessed using the COOP/Wonca charts. RESULTS: Symptoms lasting more than three months and presence of relevant psychological distress were both associated with higher levels of dyspepsia. H pylori infection, frequency of symptoms, and age had no influence on dyspepsia severity. Severity of dyspepsia and psychological distress, but not H pylori infection or duration of symptoms, affected health status univariately. Dyspepsia correlated with general health, daily activities, and social activities. In logistic modelling, health status was far better predicted by psychological distress than by dyspepsia severity. CONCLUSION: The relation between dyspeptic symptom severity and health status is limited. H pylori infection relates neither to functional health status, nor to intensity of dyspepsia. Psychological distress is a major determinant of impaired health of dyspeptic patients in general practice and may be the clue to improvement of health status in many dyspeptic patients.